2011
DOI: 10.5325/transportationj.50.4.0370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Transportation Research Journal Quality Using the Author Affiliation Index

Abstract: Previous research by Gorman and Kanet (2011) reports survey responses on transportation-related research journal quality. In addition to ranking research journal quality, respondents in that survey also provided their opinions regarding the quality of research institutions around the world. We evaluate the consistency of these two responses with the Author Affiliation Index (AAI), which evaluates journal quality by measuring the percentage of authors coming from top research institutions. We find that the AAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The original AAI formula was devised by Harless and Reilly (1998) aiming to set a minimum standard for publication outlets for the faculty at Virginia Commonwealth University, which was gradually regarded as an alternative measures of academic journal's reputation (Gorman and Kanet 2005;Chen and Huang 2007;Ferratt et al 2007;Gorman et al 2011;Chan et al 2012;Fry and Donohue 2014;Ginieis and Li 2020). The formulation of AAI can be written as…”
Section: The Original Aaimentioning
confidence: 99%
See 1 more Smart Citation
“…The original AAI formula was devised by Harless and Reilly (1998) aiming to set a minimum standard for publication outlets for the faculty at Virginia Commonwealth University, which was gradually regarded as an alternative measures of academic journal's reputation (Gorman and Kanet 2005;Chen and Huang 2007;Ferratt et al 2007;Gorman et al 2011;Chan et al 2012;Fry and Donohue 2014;Ginieis and Li 2020). The formulation of AAI can be written as…”
Section: The Original Aaimentioning
confidence: 99%
“…Subsequent to Harless and Reilly (1998), Gorman and Kanet (2005) expand the application of the AAI to the evaluation and ranking of a set of operations management journals. Since then, the AAI has been broadly employed to evaluate diverse discipline specific journals (Chen and Huang 2007;Ferratt et al 2007;Gorman et al 2011;Chan et al 2012;Fry and Donohue 2014;Ginieis and Li 2020).…”
mentioning
confidence: 99%
“…Compared with the results obtained by Guthrie et al [24], the accounting field also yielded the highest AAI score at 0.795 and displayed higher AAIs on average. Research in transportation [33] followed a similar pattern and displayed the range of AAI scores from 0.090-0.670. To further study the reasons behind such a difference in AAI scores, it is observed that there are frequently many co-authors in the same publications in journals focused on the sustainability and environmental science subject.…”
Section: Aai Rankingsmentioning
confidence: 72%
“…Author affiliations are also used to build the author affiliation index. The index was introduced in 2005 to assess journal quality (Fry & Donohue, 2014) in different academic disciplines (Chan, Tong, & Zhang, 2012;Chen & Huang, 2007;Cronin & Meho, 2008;Gorman, Kanet, & Christ, 2011;Guthrie, Everett, Vijayakumar, & Olds, 2012) and to evaluate faculty publication productivity (Maloni, Carter, & Kaufmann, 2012).…”
Section: Introductionmentioning
confidence: 99%